The Relevance of Hadith in Interpreting Qur'anic Verses on Socio-Economic Welfare through an Integrative Approach: A Perspective of Fazlur Rahman - Irwan Kurniawan; Ia Mufti Hidayat (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the relevance of Hadith in interpreting Qur'anic verses on socio-economic welfare through an integrative approach. Using the thematic exegesis method (tafsir maudhu’i) and the interconnection paradigm, this research adopts a qualitative approach with a library research design focused on analyzing primary and secondary texts. The study demonstrates how Hadith contextualizes and operationalizes Qur'anic economic principles. Key themes such as justice, zakat, the prohibition of usury, equitable wealth distribution, and social responsibility are explored from both Qur'anic and Prophetic traditions, offering a comprehensive understanding of Islamic welfare principles in the face of contemporary challenges. The findings indicate that the synergy between the Qur'an and Hadith not only provides a normative foundation but also a dynamic framework for developing sustainable and equitable economic solutions in the modern era.